United Nations Juridical Yearbook 2007 - United Nations (United Nations, 2010)
This yearbook contains documentary texts of treaties and other materials concerning the legal status and activities of the United Nations and related inter-governmental organizations. It also presents the judicial decisions on questions related to the Organization. A bibliography on jurisprudence is included.